2022
DOI: 10.7554/elife.78427
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of rapid SARS-CoV-2 genome sequencing in supporting infection control for hospital-onset COVID-19 infection: Multicentre, prospective study

Abstract: Background: Viral sequencing of SARS-CoV-2 has been used for outbreak investigation, but there is limited evidence supporting routine use for infection prevention and control (IPC) within hospital settings. Methods: We conducted a prospective non-randomised trial of sequencing at 14 acute UK hospital trusts. Sites each had a 4-week baseline data-collection period, followed by intervention periods comprising 8 weeks of 'rapid' (<48h) and 4 weeks of 'longer-turnaround' (5-10 day) sequencing using a sequence r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…While our study does not address this question, it demonstrates that Nanopore is an effective method for genotyping SNPs in the csp CTR as part of a multiplex surveillance panel, and identifies several high-frequency non-synonymous SNPs present in Ghana relative to the vaccine reference sequence. The SNP frequencies identified using ONT are very consistent with whole genome sequence data generated Experience with SARS-CoV-2 has shown that prompt turnaround time is a key factor for genomic epidemiology to be useful in clinical and public health applications [48][49][50]93]. Results are available faster if sequencing can be performed in-country, without requiring the ethical, legal and logistical framework to transport samples outside of national borders.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…While our study does not address this question, it demonstrates that Nanopore is an effective method for genotyping SNPs in the csp CTR as part of a multiplex surveillance panel, and identifies several high-frequency non-synonymous SNPs present in Ghana relative to the vaccine reference sequence. The SNP frequencies identified using ONT are very consistent with whole genome sequence data generated Experience with SARS-CoV-2 has shown that prompt turnaround time is a key factor for genomic epidemiology to be useful in clinical and public health applications [48][49][50]93]. Results are available faster if sequencing can be performed in-country, without requiring the ethical, legal and logistical framework to transport samples outside of national borders.…”
Section: Discussionsupporting
confidence: 61%
“…Experience with SARS-CoV-2 has shown that prompt turnaround time is a key factor for genomic epidemiology to be useful in clinical and public health applications [4850,93]. Results are available faster if sequencing can be performed in-country, without requiring the ethical, legal and logistical framework to transport samples outside of national borders.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid turnaround WGS and application of tools that we have used in this investigation, such as A2B Covid, genomic clustering and phylogenetics, could enable outbreaks to be disentangled in precise detail within the week that they are initiated, which may enable precise control measures to be put in place soon enough to contain the outbreak quickly. Such rapid feedback from WGS has been trialed during the second wave of COVID-19 in the UK through the Hospital Onset COVID-19 Infection (HOCI) study, which shows the effectiveness of rapid genotyping of patient infections and identification of linked cases for impacting Infection Control Procedures (Stirrup et al 2021;Stirrup et al, 2022). The limitations of this approach are that it requires easy access to WGS and specialist knowledge of bioinformatics, which may not be readily available within all hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, genomic data have been used to inform the governmental implementation of nonpharmaceutical interventions, such as national lockdown measures, to prevent viral transmission. These datasets have also been used to investigate SARS-CoV-2 transmission in hospitals and other healthcare settings, both as a rapidturnaround service to inform infection control when an outbreak occurs (Blackstone et al, 2021;Stirrup et al, 2021;Stirrup et al, 2022) and on a retrospective basis to understand the dynamics of nosocomial transmission at a larger scale (Illingworth et al, 2021;Lumley et al, 2021;Snell et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale SARS-CoV-2 sequencing programs throughout the pandemic have allowed researchers to explore the role of viral genomics and different variants of the virus. However, whilst genomic epidemiology has been used in a number of studies to understand viral transmission in settings such as hospitals [14][15][16][17], long-term care facilities [18][19][20][21][22], and army barracks [23,24], well-powered studies of patient outcomes with high numbers of cases currently remain limited [25][26][27][28][29][30][31]. One of the largest studies looking at large-scale effects of viral genomics on patient outcomes are papers from the Hospital Onset COVID-19 Infections (HOCI) study in the UK [25,26,28].…”
Section: Introductionmentioning
confidence: 99%